Smurfs in Protein Homeostasis, Signaling, and Cancer - Koganti, Praveen; Levy-Cohen, Gal; Blank, Michael (Frontiers in Oncology, 2018)
Protein ubiquitination is an evolutionary conserved highly-orchestrated enzymatic cascade essential for normal cellular functions and homeostasis maintenance. This pathway relies on a defined set of cellular enzymes, among them, substrate-specific E3 ubiquitin ligases (E3s). These ligases are the most critical players, as they define the spatiotemporal nature of ubiquitination and confer specificity to this cascade. Smurf1 and Smurf2 (Smurfs) are the C2-WW-HECT-domain E3 ubiquitin ligases, which recently emerged as important determinants of pivotal cellular processes. These processes include cell proliferation and differentiation, chromatin organization and dynamics, DNA damage response and genomic integrity maintenance, gene expression, cell stemness, migration and invasion. All these processes are intimately connected and profoundly altered in cancer. Initially, Smurf proteins were identified as negative regulators of the bone morphogenetic protein (BMP) and the transforming growth factor beta (TGF-β) signaling pathways. However, recent studies have extended the scope of Smurfs’ biological functions beyond the BMP/TGF-β signaling regulation. Here, we provide a critical literature overview and updates on the regulatory roles of Smurfs in molecular and cell biology, with an emphasis on cancer. We also highlight the studies demonstrating the impact of Smurf proteins on tumor cell sensitivity to anticancer therapies. Further in-depth analyses of Smurfs’ biological functions and influences on molecular pathways could provide novel therapeutic targets and paradigms for cancer diagnosis and treatment.